Six Years in Managing Structural Funds in Romania. Lessons Learned - Dragoş JALIU; Crina RĂDULESCU (Transylvanian Review of Administrative Sciences, 2013)
The absorption of structural and cohesion funds is one of Romania’s top priorities. Nevertheless, with a very weak absorption rate (11.47% as of December 31st 2012, according to official data), the overall situation is particularly alarming, considering the slow pace of effective project implementation and expenditure recovery from the European Commission. This text proceeds to provide an analysis of the realities of managing structural funds in Romania, focusing on the causes and factors that lead to weak absorption and on the experience of the main actors and institutions involved in this process. Our interests are, in particular, connected to the following: (1) to identify and analyze the most important aspects of structural funds management in Romania after six years of accessing and implementing projects; (2) to evaluate the capacity of the institutions involved in the structural funds management system with a focus on the level of turnover of institutions involved in the process; and (3) to identify and present added-value experiences and lessons learned from both institutions and beneficiaries (public authorities) involved in this process.